Development and validation of a novel core set of KASP markers for the traits improving grain yield and adaptability of rice under direct-seeded cultivation conditions - Sandhu, Nitika; Singh, Jasneet; Singh, Gursewak; Sethi, Mehak; Singh, Mohini Prabha; Pruthi, Gomsie; Raigar, Om Prakash; Kaur, Rupinder; Sarao, Preetinder Singh; Lore, Jagjeet Singh; Singh, Uma Maheshwar; Dixit, Shilpi; et al. (Elsevier, 2022)
The development and utilization of molecular-markers play an important role in genomics-assisted breeding during pyramiding of valuable genes. The aim of present study was to develop and validate a novel core-set of KASP (Kompetitive Allele-Specific PCR) markers associated with traits improving rice grain yield and adaptability under direct-seeded cultivation conditions. The 110 phenotypically validated KASP assays out of 171 designed KASP, include assays for biotic-resistance genes, anaerobic germination, root-traits, grain yield, lodging resistance and early-uniform emergence. The KASP assays were validated for their robustness and reliability at five different levels using diverse germplasm, segregating and advanced population, comparison with SSR markers and on F1s. The present research work will provide (i) breeding material in form of anticipated pre-direct-seeded adapted rice varieties (ii) single improved breeding line with many useful genes and (iii) KASP assay information for the useful QTL/genes providing grain yield and adaptability to rice under direct-seeded cultivation conditions.